Double-blinded infliximab dose escalation in patients with rheumatoid arthritis. Issue 9 (28th March 2007) - Rahman, Mahboob U; Strusberg, Ingrid; Geusens, Piet; Berman, Alberto; Yocum, David; Baker, Daniel; Wagner, Carrie; Han, John; Westhovens, Rene
Abstract : Objective: To determine the efficacy, safety and pharmacokinetics of infliximab dose escalation in patients with rheumatoid arthritis (RA) who had an inadequate response to 3 mg/kg infliximab treatment or whose disease flared after initially responding. Methods: Patients with active RA, despite receiving methotrexate, received infliximab 3 mg/kg at weeks 0, 2, 6 and 14 in one of the three arms of the START trial. Beginning at week 22, patients had their infliximab dose increased in a double-blind fashion in increments of 1.5 mg/kg if the total tender and swollen joint count did not improve by at least 20% from baseline (lack of response) or the improvement at week 22 or later worsened by 50% or more (criterion for flare). Results: Of the 329 evaluable patients, 100 (30.4%) patients required dose escalation at or after week 22 because of flare or lack of response. The majority of patients (>80%) who received up to three dose escalations showed ⩾20% improvement in the total tender and swollen joint count after their last dose escalation. Patients who required dose escalations generally had lower preinfusion serum infliximab concentrations than those who did not require them. The incidences of adverse events and serious adverse events for the patients who received dose escalation(s) were similar to those of patients who did not receive dose escalation. Conclusion: Fewer than one-third of patients required a dose escalation. The majority of patients showed improvement after receiving increased doses of infliximab, without an increased risk of adverse events.